Investigation of chemicomechanical properties of polyamide 12 composite reinforced with fillers from agriculture biowaste as a potential dental post - Babu, Nurul Syafika Atikah (2024)
Nanofillers and short fibres were added to polymer composites as the reinforcements to improve their mechanical properties. The synthetic E-glass fibres used in fibre- reinforced composite of commercial dental post was reported to be hazardous. Oil palm fibres and rice husk silica are cheaper and generally safer for workers than glass fibres in composite production. The aim of this research is to produce dental post and core which incorporated natural oil palm fibre (OPF) and rice husk (RH) silica from agricultural waste into the matrix and also to investigate the chemicomechanical properties of the produced post compared to the commercial post. Preparation of OPF/RH Silica/PA12 reinforced nanocomposite post was done by incorporating treated silica from rice husk and oil palm fibre crystallized nanocellulose (OPF CNC) into Polyamide 12 (PA12) matrix. Six samples with a size of 1.5mm x 2.0mm x 25.0mm were prepared for 7 groups (n=6, N=42) and six samples with the size 4mm diameter x 6mm height, were also prepared for 7 groups (n=6, N=42); Group 1 100% PA12, Group 2 PA12 (99%) + OPF CNC (1%), Group 3 PA12 (98%) + OPF CNC (2%), Group 4 PA12 (80%) + (20%) RH silica, Group 5 PA12 (80%) +(19%) RH silica + (1%) OPF CNC, Group 6 PA12 (80%) +(18%) RH silica + (2%) OPF CNC, Group 7 everStick post (flexure test)/ everX FlowTM (compressive test). The flexure and compressive tests were carried out using Instron Universal Testing Machine (Shimadzu, Japan) and the data were analysed using IBM SPSS version 26.0 (SPSS Inc, Chicago, IL, USA). Fourier- transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and Thermogravimetric analysis (TGA) were used to examine the fractured flexural strength samples. Flexural test showed that there was a statistically significant difference in flexural strength between different groups (χ2 (df) = 38.65 (6), whereby the PA12 with CNC fillers showed an increased in flexure strength value compared to unfilled PA12 and has no significant difference with commercial post. The incorporation of OPF CNC in the PA12 composite however did not increase the compressive value compared to unfilled PA12 and showed a significantly reduction in compressive strength compared to commercial composite. SEM analysis confirmed the presence of both fillers in the composite and showed smoother surface with presence of lesser voids and gaps with increment of filler wt% which suggested enhanced interfacial bonding. TGA analysis showed that OPF CNC lowered the thermostability of the composite while RH silica improved the thermostability of the composite. Incorporation of OPF CNC into PA12 matrix increased flexure strength of the composite. Incorporation of silica on the other hand reduced the flexure strength of PA12. However, the incorporation of OPF CNC or RH silica did not give any impact to the compressive strength of PA12.